Complete Healing of Severe Experimental Osseous Infections Using a Calcium-Deficient Apatite as a Drug-Delivery System - Valle, G. Amador Del; Gautier, H.; Gaudin, A.; Mabecque, V. Le; Miegeville, A.F.; Bouler, J.M.; Caillon, J.; Weiss, P.; Potel, G.; Jacqueline, C. (IntechOpen, 2011)
None